Study guide, seven simple secrets : what the BEST teachers know and do! - Breaux, Annette L.; Whitaker, Todd, 1959-; Satterfield, Nancy (New York : Routledge, 2014)
This Study Guide provides thought-provoking questions and easy-to-implement activities to help you apply the concepts in the bestselling book, Seven Simple Secrets, 2nd Edition. Step by step, it walks you through considering what you've read, taking action to implement the secrets and strategies of highly-effective teachers, and sharing your learning with others-all leading to improved teaching and learning!You can work on the guide independently, in book studies, in professional learning communities (PLCs), and in professional development sessions. This guide will help you.
Part 7: How to Find the Good in Every ChildSecret Six Summary Checklist; Secret Seven: The Secret of Motivation and Inspiration; Part 1: How to Make Your Excitement Their Excitement; Part 2: How to Make Every Student Feel Like Your Favorite Student; Part 3: How to Show Personal Interest in Every Student; Part 4: How to Maximize the Power of Praise; Part 5: How to Use Rewards Appropriately; Part 6: How to Motivate Unmotivated Students; Part 7: How to Maximize the Power of YOU; Secret Seven Summary Checklist; Conclusion; BONUS Seven!
Print version record.
eBooks on EBSCOhost
Keywords: Teaching -- Handbooks, manuals, etc; Classroom management -- Handbooks, manuals, etc; Classes (Éducation) -- Conduite -- Guides, manuels, etc; EDUCATION -- Administration -- General; EDUCATION -- Organizations & Institutions; Classroom management; Teaching; Handbooks and manuals